Optimizing Regional Potential in Tangerang Regency: Policy Recommendations Based on Cluster Analysis - Aminkun Imam Rafii (Department of Public Administration, 2023)
Tangerang Regency in Banten Province has various potential areas in each sub-district. To optimize this potential, appropriate policies are needed so that the region can develop and make a significant contribution to society. This study aims to analyze and group sub-districts in Tangerang Regency based on their regional potential using the cluster lysis analysis method with the Ward method. The results showed that sub-districts can be grouped into 5 clusters, namely Cluster 1 with the potential for rice, crops, and fisheries production; Cluster 2 with the potential for large population; Cluster 3 with the potential of many populations, area, rice, and crop production, and animal husbandry; cluster 4 with the potential of many populations, area, horticulture, and rice field land use; and cluster 5 with the potential for a large population and rice field land use. The originality of this research lies in the use of cluster analysis methods to group sub-districts based on their regional potential. The results of this study can be used as a reference for district governments in formulating appropriate policies to optimize the potential of areas in each sub-district.